Sulforaphane induces miR135b-5p and its target gene, RASAL2, thereby inhibiting the progression of pancreatic cancer - Yin, Libo; Georgikou, Christina; Herr, Ingrid (Molecular therapy. Oncolytics, 2019)
Pancreatic ductal adenocarcinoma (PDA) is one of the most lethal tumors, with poor therapeutic options in the advanced state. The broccoli-derived anti-inflammatory agent sulforaphane was shown to inhibit the progression of pancreatic cancer and other tumor entities. We examined the involvement of pancreatic cancer cell lines were evaluated by microRNA and gene expression arrays, bioinformatics, in silico analysis, qRT-PCR, western blotting, immunohistochemistry, in situ hybridization, self-renewal and differentiation assays, and in vivo xenograft studies. We selected the top nine differentially expressed microRNAs, and miR135b-5p was chosen as the most important candidate for the sulforaphane-induced upregulation of the tumor suppressor gene RASAL2. The expression of miR135b-5p and RASAL2 was almost absent in malignant pancreatic tissues and cell lines, but not in their normal counterparts. Lipofection of miR135b-5p enhanced RASAL2 expression and inhibited ERK1/2 signaling, viability, self-renewal capacity, and tumor growth. These results indicate that miR135b-5p acts as a tumor suppressor via the induction of RASAL2 in PDA.